Inflation in Pakistan: Empirical Evidence on the Monetarist and Structuralist Hypotheses (The Pakistan Development Review, 1988)
In the light of the debate between the monetarists and the structuralists regarding the explanation of inflation- in the LOCs this paper tests the monetarist and structuralist hypotheses to determine the possible factors affecting the inflationary process in Pakistan. After examining the two hypotheses the study concludes that in addition to monetary factors, the structural factors peculiar to the economy of Pakistan also have to be considered for a better understanding of this phenomenon.